Effect of Seed Coating with Polymer, Fungicide and Insecticide on Seed Quality in Sorghum (Sorghum bicolor (L.) Moench) during Storage - Rao, P. S.; Rani, M. Sudha; Ankaiah, R.; Rajasri, M.; Kumari, K. V. S. Meena (International Journal of Bio-resource and Stress Management, 2017)
The present study was undertaken with sorghum hybrid CSH 9 during 2009−10 and 2010−11 through seed coating with polymers in combination with pesticide and fungicide. The objective was to standardize the seed coating protocol for enhancement of seed quality during storage. The experiment was carried out with different seed coating materials viz., polymer coating (Polykote @ 3 ml kg-1 of seed), polymer coating+thiram 75% wp @ 2.5 g kg-1 of seed, polymer coating+imidacloprid @ 4 ml kg-1 seed, polymer coating+thiram 75% wp @ 2.5 g kg-1 of seed+imidacloprid @ 4 ml kg-1 seed and vitavax 200 @ 2 g kg-1 seed along with untreated seed. The seed material was stored in both cloth bags and 700 guage polythene bags and data was recorded on various quality parameters during storage. The results revealed that irrespective of the storage container, significantly superior germination percent (76 and 75), seedling vigour index (2895 and 2205) and field emergence (81 and 79%) was recorded with polymer coating+thiram+imidacloprid over untreated control at ten months of storage during 2009 and 10 when stored in polythene bag. There was no incidence of pathogen in the seed lots of all the treatments initially, which rose up to 4.5% in control. However, a lower per cent of infection of 0−2.5 was maintained in the seed lots stored in 700 gauge polythene bags coated with polymer coating+thiram+imidacloprid at ten months of storage. Thus, the sorghum seed treated with polymer coating+thiram+imidacloprid before storage can maintain the seed quality up to ten months of storage.